Strategi Pengelolaan Sumber Daya Alam untuk Mendukung Ekonomi Hijau di Indonesia: Penelitian - Bonaraja Purba; Jemelly Prisya Simanjuntak; Yendita Pakpahan; Jenaya Febina; Kesia Septina Putri Tarigan; Aqilah Apritia Parawanza (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Natural resource management strategies that facilitate Indonesia's transition to a sustainable green economy are a critical issue in national development. This study explores green economy policies in Indonesia and the various obstacles to their implementation through qualitative descriptive methods and a literature review of various academic sources. The findings indicate that effective natural resource management relies heavily on improved regulation, comprehensive oversight, and the active involvement of the public, private, and civil society sectors. However, challenges such as poor coordination between institutions, limited institutional capacity, and overlapping regulations continue to hamper policy effectiveness. Recommended approaches include enhancing cross-sector collaboration, providing incentives for environmentally friendly practices, and accelerating investment in renewable energy. Through integrated policies and the participation of all stakeholders, natural resource management is expected to drive economic progress that is sustainable, environmentally friendly, and socially and economically inclusive.